PENGARUH LATIHAN BOLA GANTUNG TERHADAP PENINGKATAN SMASH BOLA VOLI SISWA SMAN 2 LUWU - Al Qadri; Heri Riswanto; Rasyidah Jalil; Firmansyah Dahlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of hanging ball training on improving the volleyball smash ability of students at SMAN 2 Luwu. The method used is an experiment with a one-group pretest-posttest design. The study population was all students participating in the volleyball extracurricular at SMAN 2 Luwu, and a sample of 15 people was selected using a saturated sampling technique. The research instrument was a volleyball smash ability test conducted before and after treatment. The results showed a significant increase in students' smash ability after being given treatment in the form of hanging ball training for 16 meetings. The average pretest score of 16.87 increased to 21.80 in the posttest, with a difference in increase of 4.93 points. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. Hypothesis testing using a paired sample t-test produced a significance value of 0.001 (<0.05), so H₀ was rejected and H₁ was accepted. Thus, it can be concluded that hanging ball training has a significant effect on improving the volleyball smash ability of students at SMAN 2 Luwu. The results of this study recommend that PJOK teachers and volleyball coaches make hanging ball training one of the routine training methods to improve students' smash skills, and combine it with supporting physical training to obtain more optimal results.